Switching from intravenous to oral antibiotics in hospitalized patients with community-acquired pneumonia: A real-world analysis 2010–2018. Issue 7 (July 2020) - Kimura, Tomomi; Ito, Masanori; Onozawa, Satoshi
Abstract: The Japanese Respiratory Society 2017 guidelines strongly recommend switching from intravenous (IV) to oral antibiotics in patients with community-acquired pneumonia (CAP), following improvement in clinical symptoms and laboratory findings. Here, we retrospectively investigated the real-world, nationwide treatment and switching patterns for hospitalized patients with CAP in Japan using administrative data from 372 Japanese Diagnosis Procedure Combination hospitals from April 2010 to December 2018. Hospitalizations for CAP (patient age ≥20 years) with an A-DROP classification for CAP severity and IV antibiotics initiated on the admission date were included. Overall, 210, 314 hospitalizations (moderate CAP: 61.7%) in 183, 607 patients were analyzed. The median (interquartile range [IQR]) age at admission was 79 (70–86) years. Penicillin (51.9%) and cephalosporin (38.9%) were the most common IV antibiotic classes used and the median (IQR) duration of IV use was 8 (6–11) days. Switching to oral antibiotics during a hospitalization occurred in 30.1% (n = 63, 311) of patients after a median (IQR) of 7 (5–10) days of IV treatment. The most frequently used oral antibiotic classes after a switch were fluoroquinolone (45.9%) and penicillin (24.8%). The switch rate was higher among hospitalizations with milder CAP, in respiratory medicine ward and in larger hospitals. The overall switch rates did not change over the study period. The findings from this analysis suggest that early switch from IV to oral antibiotics was not widely implemented during the 8 years of the study period. Further observation will be needed to see the potential impact of the guidelines update in 2017 in Japan.